METHOD OF TEACHING FOREIGN LANGUAGES ON THE BASIS OF THE EDUCATION GIVEN TO A PERSON - Doston Sherov (Western European Studies, 2024)
The article deals with terminological system of language didactics taking into account its specific features from the aspects of diachronic and synchronic analyses. The main processes of formation and dynamic development of the terminological system of this science have been investigated owing to materials of the Uzbek language. However, it is important to define the role of national context in the development of language didactics by cross-cultural analysis of terminology, existing problems of comparative study of terminology and searching corresponding equivalents of these terms. The aim of the research is to improve the necessity of defining the main factors and sources of the formation and dynamic development terminological units of this science and their usage in different socio-cultural contexts, including differences in the meanings of terms of the language didactics of corresponding culture. One should be noted that close relation of language didactics with the disciplines such as didactics, methodics, pedagogy, psychology, psycholinguistics and linguaculturology is the main basis of linguistics in teaching foreign languages.
Keywords: To know the language; theory of language education